Millipedes (Diplopoda) of twelve caves in Western Mecsek, Southwest Hungary - Angyal, D.; Korsós, Z. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2013)
Twelve caves of Western Mecsek, Southwest Hungary were examined between September 2010 and April 2013from the millipede (Diplopoda) faunistical point of view. Ten species were found in eight caves, which consistedeutroglophile and troglobiont elements as well. The cave with the most diverse fauna was the Törökpince Sinkhole, while thetwo previously also investigated caves, the Abaligeti Cave and the Mánfai-kőlyuk Cave provided less species, which couldbe related to their advanced touristic and industrial utilization.